When experts disagree: interviews with public health experts on health outcomes in the UK 2010–2020 - Hiam, L; Dorling, D; McKee, M (Elsevier, 2022)
Objectives: To ascertain the views of public health experts on adverse trends in life expectancy across England and Wales over the past decade, causal factors, possible solutions, and their opinions about how the prepandemic situation influenced the UK's COVID-19 response. Study design: Semistructured, in-depth interviews. Methods: Nineteen public health experts were identified by purposeful sampling and invited to take part via e-mail. Sixty-three percent responded and participated (n = 12), six females and six males. Interviews took place via Microsoft Teams between November 2021 and January 2022. Interviews were transcribed and analysed using thematic content analysis. Results: There was no consensus on the significance of the stalling and, at some ages, reversal of previous improvements in life expectancy between 2010 and 2020. Explanations offered included data misinterpretation, widening health inequalities, and disinvestment in public services, as well as some disease-specific causes. Those accepting that the decline was concerning linked it to social factors and suggested solutions based on increased investment and implementing existing evidence on how to reduce health inequalities. These interviewees also pointed to the same factors playing a role in the UK's poor COVID-19 response, highlighting the need to understand and address these underlying issues as part of pandemic preparedness. Conclusions: There was no consensus among a group of influential public health experts in the UK on the scale, nature, and explanations of recent trends in life expectancy. A majority called for implementation of existing evidence on reducing inequalities, especially in the wake of COVID-19. However, without agreement on what the problem is, action is likely to remain elusive.